DAYA TERIMA DAN KADAR PROTEIN SERTA KALSIUM SNACKBAR SUBSTITUSI TEPUNG IKAN TERI SERTA TEPUNG KACANG MERAH - Sukmawati Sukmawati; Nadimin Nadimin; Abdullah Tamrin; Rezky Luftiannisa (Jurnal Kesehatan Manarang, 2022)
Snack bar is a snack in the form of bars using the basic ingredients of cereal and nuts. Snack bar is an option as a snack for children and teenagers because it has a soft texture and sweet taste and is not hard following children's tastes today. This study aimed to determine the receivability and content of protein and calcium snack bar substitution of anchovies and red bean flour. This study was apre-experimental study with the design of research making snack bar products with formulas of 10%, 15%, and 20% and red bean flour 20%, 30%, and 40%. The results of the hedonic test against the receiving power were analyzed using the Kruskal-Wallis test. Analysis of protein and calcium content is carried out on the best formula by the micro Kjeldahl method and the volumetric method. The receiving test showed that the most preferred anchovies and red bean flour substitution snack bar were Formula F1. Kruskal-Walis test results on aspects of colour, aroma, texture, and taste show a value of p = 0.00 (p<0.05), which means that there is a difference in preference for aspects of colour, aroma, texture and taste in snack bar substitution of anchovies and red bean flour. Based on the results of laboratory tests using the micro Kjeldahl method obtained the results of snack bar protein content substitution of anchovies and red bean flour 14.54 g/100 g and calcium content based on the results of laboratory tests using the volumetric method containing 561.5 mg/100g. Snack bar substitution of anchovies and red bean flour is most preferred by panelists from the aspect of colour, smell, texture and taste are the formula of F1. The protein content in the snack bar with the substitution of anchovies and red bean flour in formula F1 is 14.54g/100g, and calcium content is 561.5 mg/100g.